Functional reduced order H∞ decentralized observer based control for large scale interconnected nonlinear stochastic systems. Issue 2 (2020) - Barbata, Asma; Zasadzinski, Michel; Ali, Harouna Souley
Abstract: In this work, the H ∞ decentralized reduced order observer based control for a class of large scale nonlinear stochastic systems is concerned. In this context we consider subsystems which are interconnected by some nonlinear interconnections under quadratic boundedness and Lipschitz property of the system. The proposed control law is based on the resolution of some LMI.